Nutritional status of school children receiving Supplementary Feeding Program in Peninsular Malaysia - Md Arop, Mohd Shahril; Abdul Rahman, Suriah; Abdullah, Aminah; Jani, Mohd Fauzi (Penerbit Universiti Kebangsaan Malaysia, 2003)
A total of 2541 school children comprising of 1265 students who were given the School Supplementary Feeding Program (SFP) and 1276 who were not given SFP (non-SFP) aged between 7-12 years, from Central and Southern regions of Peninsular Malaysia were involved in the study. Anthropometric measurements (weight, height and triceps skinfold) and their 24-hour dietary record were assessed. Results showed that SFP subjects had a lower mean body weight (26.9 ± 7.7 kg), height (130.7 ± 10.0 em) and triceps skinfold (TSF) thickness (9.8 ± 3.8 mm) than non-SFP subjects with mean body weight29.3 ± 9.2 kg, height 132.9 ± 10.4 cm and TSF thickness 10.8 ± 4.6 mm. Chinese subjects had the highest mean body weight (28.7 ± 7.9 kg), height (132.9 ± 10.3 em) and TSF thickness (l0.3 ± 3.7 mm) amongst the SFP subjects, as well as amongst non-SFP subjects with mean body weight 31.1 ± 9.3 kg, height 135.4 ± 10.3 em and TSF thickness 11.5 ±4.9 mm. This study also showed the persistence of underweight, stunting and wasting amongst these primary school children. The prevalence of underweight amongst SFP and non-SFP subjects were 14.6% and 10.0% respectively. The prevalence of stunting was 12.6% for SFP and 7.4% for non-SFP, while wasting was found in 11.1% for SFP and 9.5% for non-SFP. The prevalence of overweight amongst SFP and non-SFP subjects were 1.3% and 4.5% respectively. Overall, only intake of protein, vitamin A and vitamin C met the RDI in all subjects for both SFP and non-SFP. Based on the findings, it can be concluded that there is a need for the Food Supplementation Program to be continuously implemented in primary schools to ensure that they will get enough food to sustain their energy.